Nonlinear Simulations of Gravity Wave Tunneling and Breaking over Auckland Island - Mixa, Tyler; Dörnbrack, Andreas; Rapp, Markus (Journal of the Atmospheric Sciences, 2021)
Large-amplitude gravity wave oscillations were observed directly above and in the lee of the Southern Ocean’s Auckland Island (50.88S, 166.18E) within the mesospheric airglow and sodium layers at ;78–83 km altitudes during research flight RF23 of the Deep Propagating Gravity Wave Experiment (DEEPWAVE)